Discursive Battles and Ideological Hegemony: A CDA of U.S. Media Headlines on Operation Epic Fury - Samuel Samuel; Resti Amalia (Yayasan Visi Intan Permata, 2026)
This study examines how the White House and CNN construct competing discourses of the Iran war through their headline narratives, and how those discourses reproduce or challenge hegemonic structures. Employing Fairclough's (1995) three-dimensional Critical Discourse Analysis, integrating micro-level transitivity and modality analysis drawn from Halliday's (1994) Systemic Functional Linguistics, meso-level discursive practice, and macro-level social practice, alongside Gramsci's (1971) conceptual framework of hegemony as an analytical instrument within the macro dimension, this study conducts a comparative analysis of twenty purposively selected headlines, ten from the White House and ten from CNN, published between March 1 and April 1, 2026, during Operation Epic Fury. The findings reveal that the White House systematically deploys material process, zero modality, nominalization, and intergenerational intertextuality to naturalize military aggression as moral common sense, while CNN progressively dismantles the conditions of that legitimacy through varied process types, verbal agency granted to Iran, and the domestication of conflict into middle-class economic reality, constituting a Gramscian war of position. Notably, this counter-hegemonic resistance is found to be driven not purely by ideological opposition but also by CNN's commercial and institutional self-interest. At the macro level, the discursive battle between these two insider institutions produces the conditions for an organic crisis, substantiated both discursively, through the White House's shift from persuasion to coercive labelling, and materially, through the documented divergence between its victory claims and independently assessed strategic outcomes.